Sistem Informasi Kepegawaian Pada PT XYZ Berbasis Website - Rahmawati, Nadiya; Mardiani, Mardiani (Universitas Multi Data Palembang, 2024)
PT XYZ has been engaged in the distribution of medical equipment since 2008 and has been a supplier of various types of medical equipment to large cities in South Sumatra and has 45 employees divided into several divisions. In personnel activities at PT XYZ there are still difficulties in the process of searching, recording, storing data and the process of applying for employee leave. The aim of developing this system is to create, add to make things easier and help several parties in carrying out existing work procedures. The method used in creating this system is RUP (Rational Unified Process) which is a software development approach that is carried out repeatedly (iterative). System design using Visual Studio Code, Laravel, MySQL as a framework with the PHP programming language. The result obtained is a website-based personnel information system that can assist in managing personnel data.